Sheep breed-specific response to environment challenge against Haemonchus contortus and effect on immuno-hematological parameters - Cintia Hiromi Okino; Hornblenda Joaquina Silva Bello; Simone Cristina Méo Niciura; Amanda Freitas da Cunha; Estevão Camilo da Costa; Emanuelle Martins de Campos; Rafaela Tami Ikeda Kapritchkoff; Lorrane Gabriele Pinheiro Corrêa; Alessandro Pelegrine Minho; Sérgio Novita Esteves; Ana Carolina de Souza Chagas (Veterinary Research Communications, 2026)
Variable resistance to Haemonchus contortus infection and the associated immune mechanisms have been investigated and characterized in different sheep breeds adapted to tropical climates. In a recent study, we compared the local immune responses of the resistant Santa Inês with those of the susceptible White Dorper and Texel sheep breeds under chronic haemonchosis, and evaluated the correlations of immune-related transcripts and different parasitic stages and sexes. The aim of present study was to further elucidate the immune mechanisms among these sheep breeds by comparing local responses, microscopic lesions in the abomasum and hematological parameters in lambs raised under varying levels of parasitic challenge. The naturally resistant Santa Inês breed maintained similar phenotypic characteristics across different levels of parasitic infection loads, whereas White Dorper and Texel breeds exhibited increased susceptibility under moderate to high challenge. Texel lambs showed altered mean corpuscular volume, indicative of macrocytic anemia, and also displayed the lowest resistance under low challenge conditions. Significantly higher levels of eosinophils, lymphocytes and monocytes in peripheral blood, along with increased expression of Galectin-11 gene in the abomasum, were observed in Santa Inês sheep compared to the other breeds. These responses may represent key host mechanisms contributing to improved control of infection. Overall, our findings demonstrate that resistance to H. contortus infection is breed-dependent and modulated by environmental parasite challenge, providing insights that may forward to the targeted strategies for sheep flock management.

Critical review of antimicrobials, antimicrobial resistance, and their associated genes in decentralized wastewater treatment systems - Mahyar Ghanadi; Mark Milke; Simone Larcher; Hamish R. Mackey; Ricardo Bello-Mendoza (Journal of Environmental Chemical Engineering, 2026)

Mapping fault architecture from depth to surface: integrating microseismicity and structural geology in low-strain Apennine regions - Giusy Lavecchia; Francesco Brozzetti; Simone Bello; Rita de Nardis (Journal of Structural Geology, 2025)

Paleoseismic evidence for the Mw∼7 1857 earthquake along the Caggiano fault system (southern Italian Apennines) - Paolo Galli; Simone Bello; Francesco Brozzetti; Antonio Galderisi; Giuseppe Naso; Antonio Pignalosa; Gianluca Benedetti; Massimo Comedini; Edoardo Peronace (Quaternary Science Reviews, 2025)

Worm replacement with susceptible Haemonchus contortus benefits weight gain, reduces anthelmintic treatments and impacts sheep breeds differently - Hornblenda Joaquina Silva Bello; Rafaela Tami Ikeda Kapritchkoff; Juliana de Carvalho Santos; Glaucia Roberta Melito; Simone Cristina Méo Niciura; Sérgio Novita Esteves; Flavia Aline Bressani; Ana Carolina de Souza Chagas (Veterinary Parasitology, 2025)

Haemonchus contortus parasitic stages development and host immune responses in lambs of different sheep breeds - Cintia Hiromi Okino; Hornblenda Joaquina Silva Bello; Simone Cristina Méo Niciura; Gláucia Roberta Melito; Amanda Freitas da Cunha; Estevão Camillo da Costa; Emanuelle Martins de Campos; Rafaela Tami Ikeda Kapritchkoff; Alessandro Pelegrine Minho; Sérgio Novita Esteves; Ana Carolina de Souza Chagas (Veterinary Immunology and Immunopathology, 2025)

Molecular signatures of Haemonchus contortus infection in sheep: A comparative serum proteomic study on susceptible and resistant sheep breeds - Ana Carolina S. Chagas; David M. Ribeiro; Hugo Osório; Ana A.P. Abreu; Cintia H. Okino; Simone C.M. Niciura; Alessandro F.T. Amarante; Hornblenda J.S. Bello; Gláucia R. Melito; Sérgio N. Esteves; André M. Almeida (Veterinary Parasitology, 2024)

Association of β-globin polymorphisms and tolerance to haemonchosis in ewes and lambs of different sheep breeds - Rafaela Tami Ikeda Kapritchkoff; Cintia Hiromi Okino; Simone Cristina Méo Niciura; Hornblenda Joaquina Silva Bello; Renata Silva Matos; Glaucia Roberta Melito; Flavia Aline Bressani; Sérgio Novita Esteves; Ana Carolina de Souza Chagas (Veterinary Parasitology, 2024)

Structural architecture and tectonic evolution of the Campania-Lucania arc (Southern Apennines, Italy): Constraints from seismic reflection profiles, well data and structural-geologic analysis - Luigi Ferranti; Filippo Carboni; Assel Akimbekova; Maurizio Ercoli; Simone Bello; Francesco Brozzetti; Alberto Bacchiani; Giovanni Toscani (Tectonophysics, 2024)

Botulinum toxin type A improves pain in numb chin syndrome - Yan Tereshko; Bruno Hector Ercole; Lettieri Christian; Enrico Belgrado; Simone Dal Bello; Merlino Giovanni; Gian Luigi Gigli; Mariarosaria Valente (Toxicon, 2024)

Botulinum toxin type a for great auricular neuralgia - Yan Tereshko; Christian Lettieri; Enrico Belgrado; Simone Dal Bello; Gian Luigi Gigli; Mariarosaria Valente (Toxicon, 2023)

Trait interactions effects on tropical tree demography depend on the environmental context - Vitor de A. Kamimura; Priscilla de P. Loiola; Carlos P. Carmona; Marco A. Assis; Carlos A. Joly; Flavio A.M. Santos; Simone A. Vieira; Luciana F. Alves; Valéria F. Martins; Eliana Ramos; Rafael F. Ramos; Francesco de Bello (Perspectives in Plant Ecology, Evolution and Systematics, 2023)

Reconciling trait based perspectives along a trait‐integration continuum - Simone Fontana; Sergio Rasmann; Francesco de Bello; Francesco Pomati; Marco Moretti (Ecology, 2021)
Trait based ecology has developed fast in the last decades, aiming to both explain mechanisms of community assembly, and predict patterns in nature, such as the effects of biodiversity shifts on key ecosystem processes. This body of work has stimulated the development of several conceptual frameworks and analytical methods, as well as the production of trait databases covering a growing number of taxa and organizational levels (from individuals to guilds). However, this breeding ground of novel concepts and tools currently lacks a general and coherent framework, under which functional traits can help ecologists organize their research aims, and serve as the common currency to unify several scientific disciplines. Specifically, we see a need to bridge the gaps between community ecology, ecosystem ecology, and evolutionary biology, in order to address the most pressing environmental issues of our time. To achieve this integration goal, we define a trait‐integration continuum, which reconciles alternative trait definitions and approaches in ecology. This continuum outlines a coherent progression of biological scales, along which traits interact and hierarchically integrate from genetic information, to whole organism fitness‐related traits, to trait syndromes and functional groups. Our conceptual scheme proposes that lower‐level trait integration is closer to the inference of ecoevolutionary mechanisms determining population and community properties, whereas higher‐level trait integration is most suited to the prediction of ecosystem processes. Within these two extremes, trait integration varies on a continuous scale, which relates directly to the inductive‐deductive loop that should characterize the scientific method. With our proposed framework, we aim to facilitate scientists in contextualising their research based on the trait‐integration levels that matter most to their specific goals. Explicitly acknowledging the existence of a trait‐integration continuum is a promising way for framing the appropriate questions, thus obtaining reliable answers and results that are comparable across studies and disciplines.